Diffraction Characteristics of Small Fault ahead of tunnel face in coal roadway (2017)
Small fault ahead of the tunnel face in coal roadway is the important hidden hazard factor of coal and gas outburst accidents. The study of small fault prediction has important practical significance, which is the urgent demand of coal mine safety production. The diffraction of breakpoint can be used to identify the fault. However, unlike surface seismic exploration, the diffraction is with approximately horizontal incidence when the advanced detection is carried out in the roadway. The common advanced detection system is mainly as the reference of traffic tunnel, without considering the influence of low-velocity coal seam. Considering the influence of an acoustic wave of the roadway cavity and channel wave of the coal seam, the advanced detection model of small fault ahead of tunnel face is established. Diffraction advanced observation system in which sources located in front of tunnel face is constructed, and the numerical calculation of the high-order staggered-grid finite difference is carried out. The simulation results show that: Compared with the data collected by reflection observation system, in seismic records acquired by diffraction observation system, the suppression effect of acoustic wave is appeared. The diffracted P-wave of the breakpoint of component X is clear with strong energy and short-wave group. Multiple diffractions of the breakpoint are not found, but the multiple diffraction of tunnel face endpoint is obvious. The difference between breakpoint diffraction and multiple diffractions of the endpoint is clear, and diffracted P-wave of the breakpoint is easy to identify. The multiple reflected channel wave between the fault and the tunnel face is very obvious, and the reflected channel wave of small fault is so hard to identify. Migration results show that the imaging resolution of diffracted P-wave of small fault is higher than the reflected channel wave, and breakpoint location of imaging is consistent with the actual model.